2007
DOI: 10.1016/j.ijcard.2006.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima-media thickness and cognition in cardiovascular disease

Abstract: Background-Increased carotid artery intima-media thickness (IMT) is a non-invasive marker of systemic arterial disease. Increased IMT has been associated with atherosclerosis, abnormal arterial mechanics, myocardial infarction, and stroke. Given evidence of a relationship between cardiovascular health and attention-executive-psychomotor functioning, the purpose of this study was to examine IMT in relation to neuropsychological test performance in patients with a variety of cardiovascular diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 37 publications
7
78
0
3
Order By: Relevance
“…The system is involved in regulating attention, switching attentional focus, and task preparation 42 and is known to be affected early in the development of vascular cognitive impairment. [43][44][45] This interpretation is supported by our present finding that greater task-related BOLD response in these regions was associated with better task performance and faster reaction times. The cross-sectional nature of our study limits our ability to infer future cognitive trajectories from the observed functional activation changes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The system is involved in regulating attention, switching attentional focus, and task preparation 42 and is known to be affected early in the development of vascular cognitive impairment. [43][44][45] This interpretation is supported by our present finding that greater task-related BOLD response in these regions was associated with better task performance and faster reaction times. The cross-sectional nature of our study limits our ability to infer future cognitive trajectories from the observed functional activation changes.…”
Section: Discussionsupporting
confidence: 72%
“…Support is provided by a growing body of literature documenting that peripheral cardiovascular dysfunction is related to poor cerebrovascular health and diminished cognitive function in older patients with cardiovascular disease. [43][44][45][51][52][53][54][55] Due to the multifaceted nature of MetS, further research is necessary to explore the contributions of frank vascular disease to the observed cognitive taskϪrelated BOLD response changes in midlife. Further exploration of other potential mechanisms such as alterations in cerebral glucose metabolism and inflammation will also be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The RBANS does not contain a measure of executive function, which is often impacted by subcortical ischemic vascular disease (Putzke et al 1998;Gunning-Dixon and Raz 2000;Saxby et al 2003;Cook et al 2004; Kramer et al 2007; Paul et al 2005;Haley et al 2007). Although neuropsychological status has not been examined in the context of A1166C, it is possible that group differences would be evident on cognitive measures inclusive of executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of postprocessing techniques are included in a previous study of the same participants . The ratio approach corrects for head size on an individual basis (Sanfilipo et al 2004) and has been utilized in previous studies of SH Haley et al 2007;Lane et al 2011;Opherk et al 2014). Previous research comparing this approach with other standardization techniques has revealed minimal to no differences in results, with no statistically superior standardization measure (Bigler et al 2004;Tate et al 2011).…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…Haley et al. (2007) reported that carotid artery stenosis was associated with worse neuropsychological performance. Recent study showed that both symptomatic and asymptomatic carotid stenosis are associated with cognitive impairment (Wang, Mei, & Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%